Repositioning To Prevent the Risk Of Decubitus using Digital Skin Moisture Tools - Muhammad Abu; Nur Halimah; Andi Wahyuni; Nursamsi; Hayyu sitoresmi (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2022)
Stroke is the biggest contributor to the risk of decubitus in health care. This incidentis due to immobilization which affects the moisture of the skin. Decubitus can worsenthe patient's quality of life and lead to death. Prevention of the risk of decubitus iscarried out by repositioning. Objective: find out the effect of repositioning on the riskof decubitus using Digital Skin Moisture. Method: quasi-experimental research with anon-equivalent control group design consisting of intervention and control groups.The sample is a stroke patient with immobilization, registered a maximum of 3x24hours of first reception. Sixty people (30 intervention groups and 30 control grouppeople) were recruited using purposive sampling techniques. The study wasconducted over 3 months (July-September 2022). Results: the Mann-Whitney testshowed that the post-test results of the intervention group experienced more skinmoisture reduction (mean-rank 23.63) compared to the control group (mean-rank37.37) with a significant value of p=0.002<p=0.05. Therefore, it was concluded thatrepositioning measures positively influenced the risk of decubitus seen from themoisture of the patient's skin. Conclusion: A stroke is a high-risk event of decubitusjudging from skin moisture. Almost all stroke patients have abnormal skin moisture.Repositioning every 2 hours has a significant effect on reducing skin moisture. Skinmoisture measurement can be used with Digital Skin Moisture Tools. This tool ishighly recommended because it can provide accurate and fast information on therisk of decubitus.Keyword: Stroke, Repositioning, Decubitus, Digital Skin Moisture Tools